SINTESIS, KARAKTERISASI DAN APLIKASI TIMAH TETRAKLORIDA PENTAHIDRAT - Marta Pramudita; Alia Badra Pitaloka; Rahmayetti Rahmayetti; Jayanudin Jayanudin; Saepurahman Saepurahman; Teguh Kurniawan; Selfira Arum Andadari (JURNAL INTEGRASI PROSES, 2023)
Indonesia is one of the world's largest tin-producing countries, but its downstream industry is not well developed. One of the chemical products derived from tin is SnCl4.5H2O. Several commercial production routes are reviewed in this paper. In addition, SnCl4.5H2O characterization techniques from advanced analytical instruments to titration analysis are also discussed. Commercial applications of SnCl4.5H2O products include catalysts, polyvinyl chloride (PVC) stabilizers, and dyes. The latest developments regarding the potential of SnCl4.5H2O as a catalyst are also reviewed in this paper.